2005
DOI: 10.2118/89364-pa
|View full text |Cite
|
Sign up to set email alerts
|

Lessons From Trinidad's CO2 Immiscible Pilot Projects

Abstract: Summary Four immiscible carbon dioxide (CO2) pilot floods were implemented in the Petroleum Co. of Trinidad and Tobago's (Petrotrin's) reservoirs at its Forest Reserve and Oropouche fields, Trinidad, over the period 1973 to 1990. The projects were conducted in a gravity-stable mode after primary, secondary, and tertiary production (after natural-gas and water injection). CO2 was injected into thick sands of variable continuity containing medium-gravity crude (17 to29°API). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Light solvents such as CO 2 , C 3 , and C 4 may also be efficient for reducing heavy oil viscosity and improving oil recovery. , An experimental pore-scale study showed bitumen dilution and production by hot C 3 and C 4 in a condensing front . Dilution of bitumen with solvent drastically reduces bitumen viscosity during SAP .…”
Section: Introductionmentioning
confidence: 99%
“…Light solvents such as CO 2 , C 3 , and C 4 may also be efficient for reducing heavy oil viscosity and improving oil recovery. , An experimental pore-scale study showed bitumen dilution and production by hot C 3 and C 4 in a condensing front . Dilution of bitumen with solvent drastically reduces bitumen viscosity during SAP .…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, this "source area" is relatively close to potential geologic storage sites. These potential sites include the spent oil fields in the Fyzabad and Oropouche areas [6] and the gas fields and saline aquifers off the east coast of Trinidad [3]. Thirdly, transportation and compression costs would be relatively lower in T&T because of the comparatively cheap cost of electricity and the close proximity of the storage sites.…”
Section: Design Conceptmentioning
confidence: 99%
“…Past CO 2 flooding projects in Trinidad illustrated a CO2 consumption rate of about 8 Mcf/bbl [6]. Given the density of CO 2 , this translates into 0.45 tonnes CO 2 to recover 1 barrel of oil.…”
Section: Assigned Volumes To Scenario 1 Co2-eor and Gcs (Combined)mentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-two percent of emissions are relatively pure streams (>95% vol) of CO 2 emitted at low pressure from seven methanol plants and 11 ammonia plants at the Point Lisas Industrial Estate (Boodlal et al 2008). Between 1973 and1990, several immiscible CO 2 pilot projects were conducted in the Forest sand found in the onshore Oropuche and Forest Reserve fields (Mohammed-Singh and Singhal 2005). CO 2 was piped 42 km and compressed in four stages, from atmospheric pressure to 68 bar (6.8 MPa), between an ammonia plant at Point Lisas and the Forest Reserve oil field.…”
Section: Introductionmentioning
confidence: 99%